Nanopore‐Based, Rapid Characterization of Individual Amyloid Particles in Solution: Concepts, Challenges, and Prospects. Issue 46 (17th September 2018) - Houghtaling, Jared; List, Jonathan; Mayer, Michael
Abstract: Aggregates of misfolded proteins are associated with several devastating neurodegenerative diseases. These so‐called amyloids are therefore explored as biomarkers for the diagnosis of dementia and other disorders, as well as for monitoring disease progression and assessment of the efficacy of therapeutic interventions. Quantification and characterization of amyloids as biomarkers is particularly demanding because the same amyloid‐forming protein can exist in different states of assembly, ranging from nanometer‐sized monomers to micrometer‐long fibrils that interchange dynamically both in vivo and in samples from body fluids ex vivo. Soluble oligomeric amyloid aggregates, in particular, are associated with neurotoxic effects, and their molecular organization, size, and shape appear to determine their toxicity. This concept article proposes that the emerging field of nanopore‐based analytics on a single molecule and single aggregate level holds the potential to account for the heterogeneity of amyloid samples and to characterize these particles—rapidly, label‐free, and in aqueous solution—with regard to their size, shape, and abundance. The article describes the concept of nanopore‐based resistive pulse sensing, reviews previous work in amyloid analysis, and discusses limitations and challenges that will need to be overcome to realize the full potential of amyloid characterization on a single‐particle level. Abstract : Information about amyloid aggregation states is critical to understanding the pathological progression of many neurodegenerative diseases. Resistive pulse‐based nanopore sensing is a unique single‐molecule approach to studying these aggregation states because it can determine information about individual amyloids, oligomeric species, or fibrils in an aqueous solution without fluorescent labels or chemical modifications.